Design and Implementation of Adaptive Hybrid Controller for the Load and Power Management of Renewable Energy-based Systems - Kumaril Buts (Majlesi Journal of Electrical Engineering)
The development of renewable energy-based applications is nowadays a forced demand of society, for chasing the target set by the governments and the concerned organizations, to reduce or limit the carbon penetration in the environment. Researchers and scholars putting their sincere efforts toward the development of efficient and reliable renewable energy-based applications. The scope of this paper is to present a Renewable Energy based Irrigation System capable of maintaining the application-based power demand. The REBIS consists of a photovoltaic generator as the main power source supported by an energy storage system (battery). For this hybrid system, the development of a utility-based Adaptive Hybrid Control is proposed to regulate the charge/discharge cycle of the battery energy while maintaining the load demand simultaneously. A case study, supporting the time-bound irrigation, is considered to verify the viability and performance of the proposed system. This proposed system and controller are first simulated in MATLAB, and then implemented at the hardware level in the LabVIEW environment.